Buddhism and the Dynamics of Transculturality New Approaches - Kellner, Birgit (Religion and Society, 2019)
For over 2500 years, Buddhism was implicated in processes of cultural interaction that in turn shaped Buddhist doctrines, practices and institutions. The contributions to this volume present detailed case studies on Buddhism's transcultural dynamics, ranging across different time periods, regions and disciplines, and addressing methodological challenges and theoretical problems.